PELATIHAN PENULISAN CERITA RAKYAT DI SDN TANGGIREJO - Khusniyah, Aziizatul; Cahyandari, Rinova (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2025)
Tanggirejo Village has a wealth of folklore that is an important part of the local cultural identity. However, modernization and social change have caused many of these folklores to be threatened with loss due to the lack of adequate documentation. This Community Service Program aims to preserve the folklore of Tanggirejo Village through writing and documentation training. This activity involves the village community, especially the younger generation and students at SDN Tanggirejo in the process of collecting, writing, and documenting local folklore. The training provided includes creative writing techniques and story documentation methods, both in written and digital forms. The results of this program are expected to be structured documentation that can be used as a reference for future generations. This program can raise awareness of the importance of preserving cultural heritage and encourage the formation of sustainable literary communities at the village level. Folklore contains various aspects of human psychology that can lead to strengthening religious moderation. Thus, this activity not only supports the preservation of folklore, but also empowers the community in maintaining and developing their local culture, as well as maintaining harmony between religious communities.